Soybean production response: A study of Jambi's acreage response under policy program. Issue 1 (July 2021) - Edison; Renate, Dharia
Abstract: Research purpose was to analyse effect of agricultural business in soybean crop. Effect government policy program has be seen through high trend of soybean production in Jambi for three decade (1986-2018). Those policy programs include support price, also input subsidy programs. Differentiation on input acreage, yield, also output has been affected by input price like fertilizer price. Successfulness policy programs can be seen through crucial indicator among important coefficients of policy programs. In some research result, it can be found some policy implications. The first policy implication stated that price support policy is much credible also important for program improvement. Impact of this program of soybean is crucial to analyse response production. In analysing acreage response, method of measuring price expectation is used when variation of market phenomena was affected by price support. Then, results also found that if support price is low from riel price, truncation effect has no effect and price support program has low effect on acreage decisions. On other hand, if price support rate is high, truncation effect is getting higher, and it is much better impact to make acreage decisions. Price soybean elasticity was 0.091 also 0.105 for short-run acreage response and long run respectively. Moreover, it was acceptable on economic and statistical aspects.